Non-coding RNAs: biological properties and ways of use - I. S. Khripkov; A. G. Dudlya (Морфологія, 2020)
RNA - one of four main macromolecules of a cell therefore certainly is a subject of the numerous researches directed to definition of its role in metabolic processes of a cell with participation of molecular mechanisms. For many years was considered that the RNA main function consists in performance of a role of the intermediary in the course of reading of the amino-acid sequence from the coding gene. Therefore opening that the sequences coding protein are less than 2% of all genome became one of the greatest surprises in modern biology; in a consequence it was established that about 90% of human genome are actively transcribed. In the overview biological properties, a way of transportation and mechanisms of influence on a cell of non-coding RNA are discussed. Non-coding RNA perform important biological function in development of organisms, their physiology and pathology. In family of non-coding RNA allocate several RNA groups which differ in origin and degree of a homology to target mRNA, have properties to inactivate at the same time several various mRNA, are highly specific inhibitors of synthesis of protein. MicroRNA regulate activity of effector molecules and play a key role in regulation of a gene expression and modulation of process of broadcasting. Participation of microRNA in regulation of processes of differentiation, proliferation, apoptosis and reaction to a stress is proved. Under control of microRNA there can be at once several regulatory ways which are responsible for a certain condition of a cell therefore disturbance of an expression of microRNA leads to dysregulation of all alarm network and disturbance of functioning of a cell. It is established that disturbance of functioning of separate types of microRNA can cause tumoral transformation, development of neurologic pathology and different types of pathology of a cardiovascular system.